Studies on the Biology of the White Grub, Holotrichia serrata Fabr. (Scarabaeidae: Coleoptera) - Amizhthini, S.; Yasodha, P.; Roseleen, S. S. J.; Satya, V. K.; Raja, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
White grub is a subterranean pest, with life cycle of about an year. Here biology of white grub is studied under laboratory conditions. Egg period lasts for 9.28 ± 0.68 days. The first instar takes about 27.88 ± 0.27 days. Second instar takes slightly longer, 35.56 ± 0.075 days and the third instar stage, takes still longer 87.72 ± 0.92 days. Pupal period averaged 27.4 ±0.24 days. Adult phase was divided into two categories. The quiescent (inactive) stage and the aerial (active) stage. The quiescent adult stage takes 83.12 ±0.06 days. Aerial stage takes 29.34 ±0.13 days. Thus, the total duration of life cycle was found to be of about 300.3 ± 2.38 days.